Co‐Immobilization of a Palladium–Bisphosphine Complex and Strong Organic Base on a Silica Surface for Heterogeneous Synergistic Catalysis. Issue 2 (3rd December 2015) - Motokura, Ken; Saitoh, Koki; Noda, Hiroto; Uemura, Yohei; Chun, Wang‐Jae; Miyaji, Akimitsu; Yamaguchi, Sho; Baba, Toshihide
Abstract: Co‐immobilization of a palladium–bisphosphine complex and a strong organic base, 1, 4‐diazabicyclo[2.2.2]octane (DABCO), on a silica support was successfully achieved. The new catalyst structure was characterized by X‐ray photoelectron spectroscopy, solid‐state NMR spectroscopy, X‐ray absorption fine structure spectroscopy, and elemental analysis. Although the local structure of the Pd–bisphosphine complex was unaffected by the presence of DABCO on the same silica surface, its catalytic activity in allylation reactions of nucleophiles was significantly enhanced, achieving turnover numbers (TON) up to >10 000, owing to dual‐activation of substrate molecules by the Pd complex and DABCO. Abstract : Stuck together : The co‐immobilization of a palladium–bisphosphine complex and 1, 4‐diazabicyclo[2.2.2]octane (DABCO) on a silica support is successfully achieved. The new catalyst structure was characterized by X‐ray photoelectron spectroscopy, solid‐state NMR spectroscopy, X‐ray absorption fine structure spectroscopy, and elemental analysis. The catalytic activity in the Pd‐catalyzed allylations of nucleophiles was significantly enhanced by having the DABCO at the same surface.